Consumers knowledge about dietary fibre : Results of a survey questionnaire in Hungary and Romania - Szűcs, V. (2016)
Dietary ﬁ bres (DFs) are essential components of the balanced diet. Even though the adequate level of their consumption can be ensured from several natural (e.g. fruit, vegetables, legumes) and ‘artiﬁ cial’ sources (e.g. functional foods), the consumed levels are below the recommendations. To analyse the Hungarian and Romanian consumers’ knowledge level, their perceptions of the health beneﬁ ts associated with ﬁ bre, as well as the recognition of the potential information sources, a survey questionnaire was conducted with the total of 713 consumers. Results showed that the level of knowledge about DFs was not adequate. Internet was found to be widely used and identiﬁ ed as one of the most appropriate information sources to encourage the consumption of DF. It was a favourable result that three-quarter of the respondents was interested in the topic of healthy food consumption; however, just less than half of them took into consideration the label information during their shopping decisions. To increase the consumption of DF and to support the responsibility and conscious consumer decisions steps must to be done (e.g. education of children, pointing out of the sources). For this purpose, modern information technology and communication channels ﬁ tting to the consumers’ cultural and personal particularities can be utilized.